A new Poptella from the rio Xingu basin, Brazil (Characiformes: Characidae) - Garcia-Ayala, James R. [UNESP]; Benine, Ricardo C. [UNESP] (FapUNIFESP (SciELO), 2023)
A new species of Poptella is described from the rio Xingu basin, Pará and Mato Grosso states, Brazil. The new species is distinguished from all congeners by having a greater number of scales around the caudal peduncle (15–18 vs. 13– 14). Furthermore, this species can be easily distinguished from P. brevispina, P. longipinnis, and P. fuscata by the lower number of branched rays in the dorsal fin (9 vs. 10–11). The description of new taxon represents the third species of the genus Poptella described in the last five years.
Keywords: Amazon; Biodiversity; Stethaprion clade; Stethaprioninae; Taxonomy